The Global South and internationalism: the geographies of post-subjectivity. Issue 4 (1st October 2020) - During, Simon
ABSTRACT: This essay argues that the concept 'Global South' belongs to the historical moment when colonialism merged into internationalism. Against that background, it begins to rethink internationalism and international relations from a postcolonial point of view. Drawing on a variegated group of theorists (Carl Schmitt, Quinn Slobodian, Pankaj Mishra) it further makes the case that the 'Global South' paradigm has to be supplemented by analysis that does not divide the world geographically or politically but takes account of generalised capitalist precarity as well as local emancipation movements disconnected from internationalism.